Innovation in distribution channel and firm performance: The case of small and medium enterprises in Indonesia / Ferri Kuswantoro - Ferri, Kuswantoro (2014)

(untitled)
It has been evidenced formany decades, that small and medium enterprises (SMEs) have become the major and fundamental contributors to employment generation, poverty alleviation,value added creation, and economic development around the globe. Due to the growing significance of internationalization, engagement in export hasdevelopedamong SMEs for seeking natural growth. Literature on export has shown that the effectiveness and efficiency of distribution channel have become critical issues for export performance. Whilst acknowledging that the characteristics of distribution channels is generally difficult to change once established, findingsfrom previous studies have strengthen the indications that firm performance is also governed by affiliation among channel members on managing coordination, avoiding conflict, achieving sales and profit, exchanging information, trusting and holding commitment, as well as how the applications of non formal channels, position of channel members; multiple distribution channels’ establishments; importers linkage establishments; and decentralization. The importance of innovation, including innovation in distribution channels as the driver of performance, is inconclusive. Additionally, such a study is extremely limited in SMEs. Therefore, this study examines the impact of innovation in distribution channel activities upon firm performance. Based on the existing literature gap, a special attentionwas given to the mediating role of distribution channel performance in the relationship between distribution channel innovation and firm performance of SMEs.This study used a sample of 120 collectedexport-oriented agriculture-based SMEsin DIY province and the surrounding areas of the Central Java, Indonesia. A hierarchical regression analysis was used to estimate the distribution channel innovation-firm performance model. Clearer findings of this study showed how the innovations led to firm performance. It was indicated that innovation in assortment, information sharing, and transportation coordination led to greater firm performance. The result of the studyalso showed that distribution performance mediated the relationship between innovations in assortment, information sharing and transportation coordination, and firm performance. This empirically proved that the effect of innovation on the performance of SMEs is strongly significant when distribution performance is enhanced through such an innovation. Thefindings and implications supportthe existing theory of transaction cost, depot theory, individual perspectives of innovation, and resource base view, which give clues for stake holders and the entrepreneurs how to engage in the innovations. It could grant challenges for the SMEs worldwide